Metode Analytic Hierarchy Process (AHP) dalam Pemilihan Penerima Beasiswa (Studi Kasus: Prodi Teknik Perangkat Lunak Universitas Universal) - Gunawan, Fery; Limuel, Patrick; Tayanto, Vincent; Purnajaya, Akhmad Rezki (Journal of Digital Ecosystem for Natural Sustainability, 2023)
Specific attention in this study is given to Universitas Universal's scholarship programs, which rely on entrance exam results for selection, prompting the exploration of more efficient and objective decision-making processes. The study draws inspiration from existing research, particularly those utilizing the Analytic Hierarchy Process (AHP), but distinguishes itself by evolving criteria to include exam scores, computer literacy, motivation, and program understanding. The primary focus is on addressing selection challenges in the software engineering program for post-admission students at Universitas Universal. By employing AHP, the study aims to provide a comprehensive decision support system, offering a prospective solution for future scholarship selection challenges. From the results of the AHP program that has been researched, it has been found that the scholarship recipient candidate is the first candidate with a score of 0.518.